Swedish taxes 1981 - Hadenius, Axel (Uppsala University, 1995)
The aim of this survey was to shed light on the Swedish people´s attitudes towards their taxes. To be able to make a special study of self-employed, particularly in questions concerning tax evasion, this group was over-represented in the sample. The study was carried out as a face to face interview where the interviewer, after concluding the interview, left a supplementary questionnaire to be filled in and returned by the respondent.

The interview contained questions on attitude toward the annual obligation to file a tax return, interest in taxation matters, discussions concerning tax regulations, opinion of the general level of taxes, and the use of tax money. The respondent had to state for what purpose the amount of tax money should be increased, kept unchanged, and reduced respectively. For a number of opinions on Swedish taxation policy the respondents had to state if they agreed or not. The respondents also had to state the kind of tax system preferred; taxes to decrease and increase respectively; attitudes toward campaigns for lowering the taxes; and if there ought to be a referendum on the size of the taxes. A number of questions concerned tax evasion, untrue tax return, and black-marketer. For a number of different crimes the respondents had to state how serious they considered them to be. Other questions dealt with the respondent´s knowledge of tax return legislations, of the level of taxes and dues, and of possibilities to influence the decisions of tax authorities, interest in politics, political preference and attitudes toward a number of opinions occurring in the political debate. Background information include occupation, share holding, education, marital status, children living at home, housing, and place of living.

Purpose:

Shed light on the Swedish people´s attitudes towards their taxes

Syftet med denna undersökning var att belysa svenska folkets inställning till sina skatter. För att kunna göra en specialstudie av företagare är denna grupp överrepresenterad i urvalet. Undersökningen genomfördes i form av besöksintervju där man efter intervjun lämnade en kompletterande enkät vilken respondenten fick i uppgift att fylla i och sända in.

Intervjun innehöll frågor om inställning till de årliga deklarationerna, intresse för skattefrågor, diskussioner om skatteregler, inställning till skatternas allmänna nivå och hur de används. Respondenterna fick ange för vilka ändamål mängden skattepengar borde ökas, hållas oförändrade eller minskas. För ett antal åsikter om svensk skattepolitik fick man ange om man instämde eller ej. Respondenterna fick även ange vilken typ av skattesystem man föredrog, vilka skatter man tycker borde höjas respektive sänkas, vilken inställning man har till protestkampanjer för att sänka skatterna och om man borde ha folkomröstning om skatternas storlek. En serie frågor berör skattefusk, falskdeklarationer och svart betalning. För ett antal olika typer av brott fick respondenten ange hur allvarligt man ansåg det vara. Övriga frågor tog upp respondentens kunskaper om deklarationsbestämmelser och skatters och avgifters höjd, möjligheter att påverka skattemyndigheters beslut, intresse för politik, politisk preferens och inställning till en serie åsikter som förekommer i den politiska diskussionen. Bakgrundsuppgifter inkluderar sysselsättning, aktieinnehav, utbildning, civilstånd, hemmavarande barn, bostadstyp och bostadsort.

Syfte:

Belysa svenska folkets inställning till sina skatter
Skatter i Sverige 1981
Keywords: FISCAL POLICY; SKATTEPOLITIK; SOCIAL WELFARE; SOCIAL VÄLFÄRD; SOCIAL WELFARE EXPENDITURE; UTGIFT FÖR SOCIAL VÄLFÄRD; TAXATION; BESKATTNING; MOONLIGHTING; SVARTARBETE; SOCIAL WELFARE FINANCE; FINANSIERING AV SOCIAL VÄLFÄRD; WELFARE ECONOMICS; VÄLFÄRDSEKONOMI; SOCIAL WELFARE PHILOSOPHY; SOCIAL VÄLFÄRDSFILOSOFI; SHARES; AKTIER; WELFARE POLICY; SOCIAL- OCH VÄLFÄRDSPOLITIK; CRIME AND SECURITY; BROTT; TAX EVASION; SKATTEFLYKT; Economic policy, public expenditure and revenue; Ekonomisk politik, offentliga utgifter och intäkter; Crime and law enforcement; Kriminalitet och rättstillämpning; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap